Formatively Assessing Expected Learning Outcomes of Undergraduate Nursing Students Enrolling Ramathibodi Nursing Curriculum Developed using Asian University Network-Quality Assurance (AUN-QA) Criteria - Thadakant, Streerut (Journal of The Royal Thai Army Nurses, 2020)
This study aims at formatively assessing students’ achievement of the Program Learning Outcomes (PLOs) which was developed using the Asian University Network-Quality Assurance (AUN-QA) Criteria. Although the PLOs were developed for students to achieve before completing the program, the expected learning outcomes for the completed second year students as the half-way of the program length were assessed. Ten expected learning outcomes which were developed based on the levels of learning from Bloom’s taxonomy were directly used as a tool comprising 5 levels of achievement ranging scales from “not achieve at all, “least achieve”, “less achieve”, “achieve”, and “most achieve”. The students were also advised to address factors for successful and unsuccessful achievement. Two hundred and twenty-three nursing students of Ramathibodi School of Nursing were recruited. It was found that 195 students (87.44%) responded to the assessment. The students identified various levels of achievement from “not achieve at all” to “most achieve” in each item. Factors as barriers and facilitators of achievement were identified. The findings can be used as inputs to develop cognitive, skills, and affective domains for students to be ready for further study and be able to achieve the program learning outcomes. The identified factors can also be brought into considerations for program revision and design.